Online Education and The Role of Teacher Empathy in Student Motivation - Yahya Gordani; Mahnaz Ezhdehakosh; Kimia Mansouri; Elham Abbasi (Journal of Pedagogical and Teacher Professional Development, 2026)
Empathy has been recognized as one of the crucial elements in social and behavioral sciences. As a multidimensional phenomenon, empathy helps individuals share emotions and understand others’ emotional reactions. Online learning platforms, as one of the popular learning environments, should also be led with a proper pedagogy, regulating teachers to practice certain pedagogical practices to address students’ emotions and express emphatical responses. Nevertheless, it has often been reported that online learning due to social distancing and lack of certain psychological factors induces unfavorable results. Using a mixed-method research design, present study sought to take a serious look at the focal role of teacher empathy in pedagogical contexts and its effect on student motivation in online learning environments. To this aim, the Toronto empathy questionnaire  was administered to ten university assistant professors at two universities. Simultaneously, a number of students of teacher participants (n=60) filled out the academic motivation scale. Student participants were also interviewed to reflect on the empathetical aspects of their teachers' performance in online classes. Findings from the quantitative (correlation and regression) analyses of the data as well as the qualitative analyses of the interviews, demonstrated that the explicit demonstration of empathy in classrooms elevates students' motivation for learning. The study highlights the importance of prioritizing the demonstration of empathy in educational ecology.